РОЗВИТОК ІНФОРМАЦІЙНО-КОМУНІКАЦІЙНОЇ КОМПЕТЕНТНОСТІ ВЧИТЕЛЯ У ГАЛУЗІ СЕРЕДНЬОЇ ОСВІТИ НІДЕРЛАНДІВ: ПІДХОДИ, МОДЕЛІ, ДОСВІД - Grytsenchuk, Olena O. (Information technologies and learning tools, 2015)
The article deals with the problem of teacher’s information and communication competence development in general secondary education of the Netherlands. The analysis of the experience of such national institutions as Expertise Centre of ICT Education, Fund Kennisnet, SchoolNet of the Netherlands, Netherlands Institute for Curriculum Development (SLO), General Consultative Body of Heads of Teachers Educational Faculties is presented. There are identified peculiarities, common trends, approaches and models of teacher’s information and communication competence, as well as the ways of teacher’s information and communication competence future development in general secondary education of the Netherlands. В статье освещается проблема развития информационно-коммуникационной компетентности учителя учебного заведения системы общего среднего образования Нидерландов. Представлен анализ опыта таких национальных институций как Центр экспертизы обучения ИКТ, фонд Kennisnet, SchoolNet Нидерландов, Институт развития содержания образования Нидерландов (SLO), Консультативный совет руководителей педагогических факультетов. Приводятся общие подходы и представлены модели информационно-коммуникационной компетентности учителя общеобразовательного учебного заведения, раскрыто их сущность, выделены проблемные аспекты, особенности, общие тенденции и пути развития ИК-компетентности учителя учебного заведения системы общего среднего образования Нидерландов. У статті висвітлюється проблема розвитку інформаційно-комунікаційної компетентності учителя навчального закладу системи загальної середньої освіти Нідерландів. Подано аналіз досвіду таких національних інституцій як Центр експертизи навчання з ІКТ, фонд Kennisnet, SchoolNet Нідерландів, Інститут розвитку змісту освіти Нідерландів (SLO), Консультативна рада керівників педагогічних факультетів. Подано загальні підходи та представлено моделі інформаційно-комунікаційної компетентності учителя загальноосвітнього навчального закладу, розкрито їх сутність, виокремлено проблемні аспекти, особливості, загальні тенденції та шляхи розвитку ІК-компетентності учителя навчального закладу системи загальної середньої освіти Нідерландів.